2016
DOI: 10.5812/asjsm.38318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lateral Abdominal Muscle Thickness and Cross Sectional Area of Multifidus in Adolescent Soccer Players with and without Low Back Pain: A Case Control Study

Abstract: BackgroundLow back pain (LBP) is a common complaint amongst adolescent athletes. While different studies have shown association between LBP and trunk muscle thickness in the general population, few articles have studied it in adolescent athletes.ObjectivesThe aim of this study is to compare lateral abdominal muscle thickness and function, and cross sectional area (CSA) of lumbar multifidus (LM) in adolescent soccer players with and without LBP.MethodsIn total, 28 adolescent soccer players with and without LBP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 42 publications
5
31
0
Order By: Relevance
“…Our baseline results also showed no difference in percent thickness change due to contraction in the muscles of the lateral abdominal wall between the patients with LBP and the healthy controls (Table ). Previous RUSI measures of EO and IO activation have also found no differences between these groups . Previous findings for TrA activation, however, are heterogeneous, with different studies showing negative (no difference) and positive findings .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our baseline results also showed no difference in percent thickness change due to contraction in the muscles of the lateral abdominal wall between the patients with LBP and the healthy controls (Table ). Previous RUSI measures of EO and IO activation have also found no differences between these groups . Previous findings for TrA activation, however, are heterogeneous, with different studies showing negative (no difference) and positive findings .…”
Section: Discussionmentioning
confidence: 79%
“…Previous RUSI measures of EO and IO activation have also found no differences between these groups. 36,39,44 Previous findings for TrA activation, however, are heterogeneous, with different studies showing negative (no difference) 39,45 and positive findings. 35,36,44,46 The sample of patients with nonspecific LBP that was recruited for the present study might show other neuromuscular impairments.…”
Section: Between-group Comparisonsmentioning
confidence: 98%
See 1 more Smart Citation
“…No association between LLD and LBP in our study is in accordance with prior studies. Noormohammadpour et al (2016) evaluated a small sample of 28 adolescent football players and reported that LBP had no link with LLD. A study by Goss, Moore, Slivka, & Hatler (2006) involved 1100 military cadets and match controls aft er 1-year participation in military training and athletic participation.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies which have used musculoskeletal ultrasonography in athletes. It has been used in the evaluation of transabdominal and paraspinal muscles in adolescent (6) and young (7) soccer players with/without low back pain. Researchers have also tracked muscle changes with musculoskeletal ultrasonography among soccer players during a season with and without developing low back pain (8).…”
mentioning
confidence: 99%